Understandability and actionability of audiovisual patient education materials on sinusitis. Issue 4 (12th January 2020) - Rubel, Kolin E.; Alwani, Mohamedkazim M.; Nwosu, Obi I.; Bandali, Elhaam H.; Shipchandler, Taha Z.; Illing, Elisa A.; Ting, Jonathan Y.
Abstract : Background: Acute and chronic rhinosinusitis are debilitating diseases that affect from 5% to 16% of the population. YouTube is the second most commonly used search engine and is often utilized by patients to garner health information regarding various disease processes and their respective management options. An evaluation of these information resources for quality and reliability is warranted, especially in an era in which patients are increasingly turning to audiovisual (A/V) media to educate themselves regarding their ailments. Methods: The YouTube video database was searched using the term "sinusitis" from its inception through to November 2018. The first 50 videos populated under the relevance‐based ranking option were collected and parsed by time and language. Of the 50 videos, 10 were eliminated either for length (≤1 minute or ≥20 minutes), language (any language other than English), and/or for later being removed by YouTube for copyright violations. The videos were then assessed using the Patient Education Materials Assessment Tool―Audio/Visual (PEMAT‐A/V) by 2 independent reviewers for understandability and actionability. Results: A total of 40 videos were examined using the PEMAT‐A/V tool. The average understandability score was 57.7%, whereas the average actionability score was 46.3%. Eleven videos (28%) had actionability scores of 0%. Videos most commonly addressed disease management options (38%). The second largest category was case presentations regarding surgical techniques (30%). There were only 6 videos focused primarily on education about the definition and common traits of sinusitis (15%). Conclusion: Our results show a paucity of high‐quality online A/V educational material pertaining to sinusitis, with a majority of videos being neither understandable nor actionable. As patients increasingly turn to internet video databases like YouTube for medical information, it is critical that physicians and institutions create A/V material that is accurate, understandable, and actionable.